2016
DOI: 10.1177/1477153516666132
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the nature of visual fixations on other pedestrians

Abstract: How we look at other people may affect conclusions drawn about the effect of changes in lighting when this task needs to be done after dark. This paper reports further analysis of the distance and duration of fixation on other pedestrians, updating a previous review by considering a greater number of fixations and by examining the influence on these of other characteristics such as the relative direction of travel. This analysis provides further support for a tendency to fixate others at a distance of 15 m and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Other studies, however, concluded that there is a significant effect of SPD 137,160 and these data contributed to an assumed benefit of better colour quality in revised guidance. 68 Subsequent research first examined methodology, proposing that different procedures may lead to different conclusions, 161,162 that facial emotion recognition from expression is a more suitable task than identify recognition, [163][164][165] that a brief duration of 500 ms better resembles typical behaviour than does continuous observation, 166,167 and that the stop-distance approach used in many studies may not lead to the same conclusions as evaluations made at the desirable observation distance of 15 m. 166,167 In studies carried out using facial emotion recognition, SPD is not suggested to be a critical parameter. [168][169][170][171] One question still to be resolved is whether a measure of vertical illuminance is needed to characterise this task or whether it is safe to assume that horizontal illuminance at the road surface is sufficient.…”
Section: Comparing Approachesmentioning
confidence: 99%
“…Other studies, however, concluded that there is a significant effect of SPD 137,160 and these data contributed to an assumed benefit of better colour quality in revised guidance. 68 Subsequent research first examined methodology, proposing that different procedures may lead to different conclusions, 161,162 that facial emotion recognition from expression is a more suitable task than identify recognition, [163][164][165] that a brief duration of 500 ms better resembles typical behaviour than does continuous observation, 166,167 and that the stop-distance approach used in many studies may not lead to the same conclusions as evaluations made at the desirable observation distance of 15 m. 166,167 In studies carried out using facial emotion recognition, SPD is not suggested to be a critical parameter. [168][169][170][171] One question still to be resolved is whether a measure of vertical illuminance is needed to characterise this task or whether it is safe to assume that horizontal illuminance at the road surface is sufficient.…”
Section: Comparing Approachesmentioning
confidence: 99%
“…Given that observation duration affects the chance of correct facial identity recognition, 47 then further research should at least include a duration of 500 ms. Eye-tracking data suggest a mean tendency to look at other people 2.4 times, 101 although the nature of these repeated fixations was not established. Overall, this is 1.2 s observation, which indicates that the stop-distance procedure used in some past studies of lighting (Table 1) is not realistic as it instructs an observation of longer (likely continuous) duration.…”
Section: Observation Durationmentioning
confidence: 96%
“…99 Consider next evidence as to the typical time desired for looking at other people. Two studies 100,101 investigated this using the data recorded in a pedestrian eye-tracking study, 8 including the duration of visual fixations towards other people. These studies reported a median of 480 ms, 100 and a mean of 475 ms, 101 the latter using a larger data set comprising 5955 fixations towards 2496 pedestrians.…”
Section: Observation Durationmentioning
confidence: 99%
See 2 more Smart Citations